Culturable Bacterial Endophytes of Wild White Poplar (Populus alba L.) Roots: A First Insight into Their Plant Growth-Stimulating and Bioaugmentation Potential - Natalya S. Gladysh; Alina S. Bogdanova; Maxim A. Kovalev; George S. Krasnov; Vsevolod V. Volodin; Anastasia I. Shuvalova; Nikita V. Ivanov; Mikhail I. Popchenko; Aleksandra D. Samoilova; Aleksandra N. Polyakova; Alexey A. Dmitriev; Nataliya V. Melnikova; et al. (Biology, 2023)
The white poplar (Populus alba L.) has good potential for a green economy and phytoremediation. Bioaugmentation using endophytic bacteria can be considered as a safe strategy to increase poplar productivity and its resistance to toxic urban conditions. The aim of our work was to find the most promising strains of bacterial endophytes to enhance the growth of white poplar in unfavorable environmental conditions. To this end, for the first time, we performed whole-genome sequencing of 14 bacterial strains isolated from the tissues of the roots of white poplar in different geographical locations. We then performed a bioinformatics search to identify genes that may be useful for poplar growth and resistance to environmental pollutants and pathogens. Almost all endophytic bacteria obtained from white poplar roots are new strains of known species belonging to the genera Bacillus, Corynebacterium, Kocuria, Micrococcus, Peribacillus, Pseudomonas, and Staphylococcus. The genomes of the strains contain genes involved in the enhanced metabolism of nitrogen, phosphorus, and metals, the synthesis of valuable secondary metabolites, and the detoxification of heavy metals and organic pollutants. All the strains are able to grow on media without nitrogen sources, which indicates their ability to fix atmospheric nitrogen. It is concluded that the strains belonging to the genus Pseudomonas and bacteria of the species Kocuria rosea have the best poplar growth-stimulating and bioaugmentation potential, and the roots of white poplar are a valuable source for isolation of endophytic bacteria for possible application in ecobiotechnology.